RESILIÊNCIA EM GESTÃO DE PESSOAS: UM ESTUDO A PARTIR DA APLICAÇÃO DO QUESTIONÁRIO DO ÍNDICE DE RESILIÊNCIA: ADULTOS EM GESTORES DE UMA ORGANIZAÇÃO DE GRANDE PORTE - Bedani, Edna Rodrigues (2008)
The current context of organizations is permeated with pressures, crisis and uncertainties, characteristics of the globalization era, which require the human capacity to adapt. The constant confrontation of unstable situations needs, in any relational level, what is known as resilience. Nowadays, the use of this term is growing due to its applicability in the study of the human capacity to resist intense pressure situations. The term resilience was developed from studies of population in a state of risk and vulnerability, and nowadays has been the topic of some discussions on the organizational field. Based on this concept, the purpose of this work is to study the resilience in people managers, in a large scale profit-driven organizations, for the services industry in São Paulo, starting from the application of the Resilience Index Questionnaire: Adultos - Reivich-Shatté/Barbosa (2006). The adopted research methodology is of exploratory and descriptive character. The used instrument favored the measurement of the seven factors constituent of resilience in human behavior, which are: emotional administration, impulse control, optimism towards life, ambient analysis, empathy, self-efficiency and reaching people. The results obtained show that it is possible to study the resilience in people managers, by the use of the proposed instrument. This work also allowed the association of the factors that constitute resilience with some essential competences necessary for a people manager to properly carry out his activities, without neglecting the leadership aspects associated with his function.(AU)